Maximum Heart Rate during exercise: Reliability of the 220-age and Tanaka formulas in healthy young people at a moderate altitude (2014)
Background. The formulas to predict maximum heart rate have been used for many years in different populations.Objective. To verify the significance and the association of formulas of Tanaka and 220-age when compared to real maximum heart rate.Materials and methods. 30 subjects –22 men, 8 women– between 18 and 30 years of age were evaluated on a cycle ergometer and their real MHR values were statistically compared with the values of formulas currently used to predict MHR.Results. The results demonstrate that both Tanaka p=0.0026 and 220-age p=0.000003 do not predict real MHR, nor does a linear association exist between them.Conclusions. Due to the overestimation with respect to real MHR value that these formulas make, we suggest a correction of 6 bpm to the final result. This value represents the median of the difference between the Tanaka value and the real MHR. Both Tanaka (r=0.272) and 220-age (r=0.276) are not adequate predictors of MHR during exercise at the elevation of Bogotá in subjects of 18 to 30 years of age, although more study with a larger sample size is suggested.